Cell surface-expressed Ro52/IgG/HLA-DR complex is targeted by autoantibodies in patients with inflammatory myopathies. Issue 126 (January 2022) - Arase, Noriko; Tsuji, Hideaki; Takamatsu, Hyota; Jin, Hui; Konaka, Hachiro; Hamaguchi, Yasuhito; Tonomura, Kyoko; Kotobuki, Yorihisa; Ueda-Hayakawa, Ikuko; Matsuoka, Sumiko; Hirano, Toru; Yorifuji, Hideki; et al.
Abstract: Intracellular proteins are often targeted by autoantibodies in autoimmune diseases; however, the mechanism through which intracellular molecules are targeted remains unknown. We previously found that several intracellular misfolded proteins are transported to the cell surface by HLA class II molecules and are recognized by autoantibodies in some autoimmune diseases, such as rheumatoid arthritis, antiphospholipid syndrome, and microscopic polyangiitis. Ro52 is an intracellular Fc receptor that is a target antigen for myositis-associated autoantibodies. We analyzed the role of HLA class II molecules in the autoantibody recognition of Ro52. Ro52 alone was not transported to the cell surface by HLA class II molecules; however, it was transported to the cell surface in the presence of both IgG heavy chain and HLA class II molecules to form a Ro52/IgG/HLA-DR complex. The Ro52/IgG/HLA-DR complex was specifically recognized by autoantibodies from some patients with inflammatory myopathies. We then evaluated 120 patients with inflammatory myopathies with four types of myositis-specific antibodies and analyzed the autoantibodies against the Ro52/IgG/HLA-DR complex. The specific antibodies against the Ro52/IgG/HLA-DR complex were detected in 90% and 93% of patients who were positive for anti-MDA5 and anti-ARS antibodies, respectively. In individual patients with these two inflammatory myopathies, changes in serum titers of anti-Ro52/IgG/HLA-DR-specific antibodies were correlated with the levels of KL-6 (R = 0.51 in anti-MDA5 antibody-positive DM patients, R = 0.67 in anti-ARS antibody-positive PM/DM patients with respiratory symptoms) and CK (R = 0.63 in anti-ARS antibody-positive PM/DM patients with muscle symptoms) over time. These results suggest that antibodies against Ro52/IgG/HLA-DR expressed on the cell surface could be involved in the pathogenesis of inflammatory myopathy subgroups. Graphical abstract: Image 1 Highlights: Ro52 bound to IgG/HLA-DR complex is transported to the cell surface. Anti-Ro52/IgG/HLA-DR-specific antibody is detected in anti-MDA5 and anti-ARS antibody-positive DM. Sequential changes in anti-Ro52/IgG/HLA-DR-specific antibody titers correlated with individual DM activities. Ro52/IgG/HLA-DR complex on the cell surface could be involved in the pathogenicity of DM.